Studi Penempelan Juvenil Karang Pocillopora damicornis Pada Jenis Substrat Kolektor Dan Zona Terumbu Yang Berbeda Di Pulau Panjang, Kabupaten Jepara - Kisworo, Hendro; Wijayanti, Diah Permata; Munasik, Munasik (977-2407769)
Coral reef at Panjang Island is being gradually degraded. At least, the availability of substrates that suitable for coral’s attachment has a great effect to coral abundance. The aim of this research is to know coral juvenile’s recruitment (Pocillopora damicornis) based on the abundance of coral juvenile which attaches on the different location (zone), placement (position), type of substrate, and time of observation. This experimental research was carried out on August-November 2009 at Panjang Island, Jepara. The research uses substrate from Cement Block and Andesite Stone placed on the column and bottom of water at reef flat and reef slope zone. The result shows that coral juvenile abundance rise significantly along with time rising. Abundance of coral juvenile also different between coral zones, P.damicornis juvenile on reef flat zone is more higher (86 colonies founds), than reef slope zone (64 colonies founds). This is because the substrate in reef slope zone was far from adult coral colonies which produce planula, whereas in reef flat zone there was much found adult coral colonies.